(untitled) (World Economics and Finance Bulletin, 2025)
Rhetorical studies of the Mighty Book of God are considered for the sake of studies, the most important of which are, as they highlight the linguistic and rhetorical miracle of the Great Qur’an. Rhetorical overlap and juxtaposition are among the rhetorical methods that contribute to the cohesion and cohesion of the literary text, and add coherence and good organization and arrangement. The Holy Qur’an is rich in graphic images that overlap or juxtapose with methods related to the science of meanings and the beautiful, In a vibrant style, imbued with imagination when drawing the artistic rhetorical scene that perfectly expresses the intended idea. The intended idea in this research is the images of the otherworldly torment that awaits those who are called to faith, but they refuse and become arrogant, so the messengers approached him with admonition, guidance, and guidance, but he became arrogant, so the Lord of the Worlds threatened him with an evil fate on the Day of Judgment.